Advanced Transport Systems Analysis, Modeling, and Evaluation of Performances - Janić, Milan (Springer London : Imprint: Springer, 2014)
This book provides a systematic analysis, modeling and evaluation of the performance of advanced transport systems. It offers an innovative approach by presenting a multidimensional examination of the performance of advanced transport systems and transport modes, useful for both theoretical and practical purposes. Advanced transport systems for the twenty-first century are characterized by the superiority of one or several of their infrastructural, technical/technological, operational, economic, environmental, social, and policy performances as compared to their conventional counterparts. The advanced transport systems considered include: Bus Rapid Transit (BRT) and Personal Rapid Transit (PRT) systems in urban area(s), electric and fuel cell passenger cars, high speed tilting trains, High Speed Rail (HSR), Trans Rapid Maglev (TRM), Evacuated Tube Transport system (ETT), advanced commercial subsonic and Supersonic Transport Aircraft (STA), conventionally- and Liquid Hydrogen (LH2)-fuelled commercial air transportation, advanced Air Traffic Control (ATC) technologies and procedures for increasing the airport runway capacity, Underground Freight Transport (UFT) systems in urban area(s), Long Intermodal Freight Train(s) (LIFTs), road mega trucks, large advanced container ships and freight/cargo aircraft, and advanced freight/goods collection distribution networks. This book is intended for postgraduates, researchers, professionals and policy makers working in the transport industry.